Antibacterial property of super oxide water - Abesamis, Pamela L.; Serraon, Antolin (Adviser).
Super Oxide Water is the product of the latest research in Japan. The Japanese claims that this product can inhibit the growth of pathogenic microorganisms. It is believed that the mechanism of bactericidal effect of this water involves the synergism among low pH, high oxidation-reduction potential and low chlorine concentration. The objective of the study was to determine the antibacterial property of Super Oxide Water at different concentrations. For this purpose, the researcher used a qualitative type of experiment. A turbidity of 0.5 McF (McFarland) Staphylococcus aureus was prepared. Nine (9) ml of each concentration of Super Oxide Water was mixed with one (1) ml 0.5 McF S. aureus for one minute contact time. Ten (10) ul (microliter) of the solution was obtained and dropped in the blood agar plate. Three trials, each with a duplicate, were done for each concentration. The plates were then incubated for 24 to 48 hours. After the incubation period, it was observed that from 100% up to 25% concentration, Super Oxide Water was able to inhibit the growth of S. aureus since no growth occurred. From 20% concentration and below, most of the replicas registered positive for growth. Based on these findings, the author conclude that Super Oxide Water has an antibacterial action against S. aureus at 25% -100% concentration and that the degree of inhibition is proportional to concentration.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.